2016
DOI: 10.1111/jjns.12108
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of Indonesian nurses in Japan: A phenomenological study

Abstract: The results of this study call for further intervention in supporting Indonesian nurses living in Japan in their struggle with the issue of communication. The emphasis on language acquisition for personal and professional objectives, and the bridging of cultural differences as well, should be considered in an international context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…Returnees’ positive influences from their work experience were also confirmed in a previous study by Efendi et al. (), which found that Indonesian migrant nurses in Japan adopted discipline as a work ethic and way of life.…”
Section: Discussionsupporting
confidence: 78%
“…Returnees’ positive influences from their work experience were also confirmed in a previous study by Efendi et al. (), which found that Indonesian migrant nurses in Japan adopted discipline as a work ethic and way of life.…”
Section: Discussionsupporting
confidence: 78%
“…The underlying economic motives of participants migrating are based on the desire to earn a higher stipend and to increase their welfare, while the main factors encouraging nurses to work abroad are the family's economic condition and the low salary earned in the country of origin. This was in accordance with studies which mentioned economic considerations as the main driver in nurse migration (Dywili et al, 2013;Efendi et al, 2016;Nursalam et al, 2020). Social motives involved the privileged status -as Indonesian nurses were recruited and hired at facilities owned by the Government of Kuwait.…”
Section: Discussionsupporting
confidence: 84%
“…This system may disappoint EPA nurses. In fact, obtaining a high level of proficiency in the Japanese language is one of the biggest challenges for EPA nurses [ 15 , 16 , 18 ]. Differences in language, aside from differences in culture-based lifestyle, are considered barriers to the adjustment of Filipino [ 19 ], Chinese [ 20 ], Jordanian [ 21 ], and nurses of different nationalities who migrate to other countries [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%